Impact of Thermo‐Physical Data on the Modeling of High‐Pressure Polymerizations1. Issue 11 (12th August 2016) - Pflug, Kristina Maria; Busch, Markus
Abstract: Modeling the high‐pressure polymerization of ethene is of vital importance in order to avoid costly high‐pressure experiments when it comes to process optimization and product design. However, closing the heat balance when modeling high‐pressure tubular reactors with a counter‐current jacket cooling is still difficult. In this contribution the influence of thermo‐physical properties – namely viscosity and heat capacity – on the simulation results was investigated. Various literature sources were evaluated and a variety of simulations were conducted, showing that both properties influence the resulting temperature profiles and conversions visibly, while the molecular weight distribution was not affected. Uncertainties of the heat capacity of 5 % could be compensated by varying initiator efficiency and fouling layer thickness within physically reasonable boundaries. Abstract : The influence of mixture viscosity and heat capacity on the process modeling of high‐pressure polymerization of ethene in tubular reactors is evaluated. Special attention is paid to the heat balance, the conversion and the properties of the resulting LDPE mainly depicted by the molecular weight distribution.